High‐Rate Charging Induced Intermediate Phases and Structural Changes of Layer‐Structured Cathode for Lithium‐Ion Batteries. Issue 21 (8th August 2016) - Zhou, Yong‐Ning; Yue, Ji‐Li; Hu, Enyuan; Li, Hong; Gu, Lin; Nam, Kyung‐Wan; Bak, Seong‐Min; Yu, Xiqian; Liu, Jue; Bai, Jianming; Dooryhee, Eric; Fu, Zheng‐Wen; et al.
Abstract : Using fast time‐resolved in situ X‐ray diffraction, charge‐rate dependent phase transition processes of layer structured cathode material LiNi1/3 Mn1/3 Co1/3 O2 for lithium‐ion batteries are studied. During first charge, intermediate phases emerge at high rates of 10C, 30C, and 60C, but not at low rates of 0.1C and 1C. These intermediate phases can be continuously observed during relaxation after the charging current is switched off. After half‐way charging at high rate, sample studied by scanning transmission electron microscopy shows Li‐rich and Li‐poor phases' coexistence with tetrahedral occupation of Li in Li‐poor phase. The high rate induced overpotential is thought to be the driving force for the formation of this intermediate Li‐poor phase. The in situ quick X‐ray absorption results show that the oxidation of Ni accelerates with increasing charging rate and the Ni 4+ state can be reached at the end of charge with 30C rate. These results give new insights in the understanding of the layered cathodes during high‐rate charging. Abstract : Intermediate phases are revealed in LiNi1/3 Mn1/3 Co1/3 O2 (NMC) cathode during charge at 10C rate, and become more pronounced at 30C and 60C. Li tetrahedral site occupation becomes possible when high rates are applied. The charge compensation contribution by Ni ions is faster and more effective at higher C rate, suggesting the benefit of higher Ni content in NMC for rate capability.